"The Textual Approach in Grammar Pedagogy: Between Theory and Practice" - .hrizi, lakdar (El Omda in Linguistics and Discourse Analysis, 2018)
The pedagogy of Arabic grammar is considered one of the most important topics that has occupied the thinking of many scholars of the Arabic language, particularly regarding the facilitation of teaching grammar in Arab schools. This need arose as learners increasingly became reluctant to study Arabic grammar due to its difficulties and the disagreements among various grammatical schools. Among the modern methods adopted by the Algerian educational system in teaching grammar is what is called the textual approach, in which grammatical phenomena are taught within their textual context rather than in isolated phrases or sentences. The main challenge highlighted by specialists in this field is the extent to which this approach can be effectively applied in practice. Language pedagogy has a close, reciprocal connection with many different sciences, foremost among them linguistics, from which pedagogy draws everything beneficial for learners in acquiring language.